Single Nanoskived Nanowires for Electrochemical Applications - Dawson, K.; Strutwolf, J.; Rodgers, K.; Herzog, G.; Arrigan, Damien; Quinn, A.; O’Riordan, A. (American Chemical Society, 2011)
In this work, we fabricate gold nanowires with well controlled critical dimensions using a recently demonstrated facile approach termed nanoskiving. Nanowires are fabricated with lengths of several hundreds of micrometers and are easily electrically contacted using overlay electrodes. Following fabrication, nanowire device performance is assessed using both electrical and electrochemicalcharacterization techniques. We observe low electrical resistances with typical linear Ohmic responses from fully packaged nanowire devices. Steady-state cyclic voltammograms in ferrocenemonocarboxylicacid demonstrate scan rate independence up to 1000 mV s1. Electrochemical responses are excellently described by classical ButlerVolmer kinetics, displaying a fast, heterogeneous electron transfer kinetics, k0 = 2.27 ( 0.02 cm s1, R = 0.4 (0.01. Direct reduction of hydrogen peroxide is observed at nanowires across the 110 pMto 1 mM concentration range, without the need for chemical modification, demonstrating the potential of these devices for electrochemical applications.